NEUROPHYSIOLOGY AND SIGNALING PATHWAYS OF MEMORY - Stankovic Matic, Ivana B (Medicinski časopis, 2017)
An important starting step in understanding neurobiology of memory lies in identifying locations of physical and chemical changes that follow cognition. As Hebb indicated, and as shown on computer models, memory is a consequence of subtle alterations in synapses. Synaptic response is not invariant, but can be altered by a variety of homo and heterosynaptic factors, such as modulatory neurotransmitters. This approach helps branching the search for the very physiology of memory – synaptic modification, but rises many questions about modulation of synaptic transmission. The synaptic modification associated with memory capacity can be too small and too widely distributed in the brain, which consequently makes observation and experimental studies more difficult. Explorations of nervous system in invertebrates proved Hebb’s theory that memories can be formed by synaptic alterations, therefore it’s also possible to identify some molecular mechanism that lead to this synaptic plasticity. Although nonsynaptic changes may also occur in studies of certain types of memory, there is little doubt that the synapse is an important location of information storage. Hipoccampus is confirmed in declarative memory ( explicit type, relational type of memory). In this work there is biological perspective that propose memory systems with different functions and dinstinct anatomical organization. Interdisciplinary approach is of great importance for complete understanding of the very physical basis of memory.